"We're building their data": Labor, alienation, and idiocy in the smart city. (December 2019) - Attoh, Kafui; Wells, Katie; Cullen, Declan
In 2017, Uber Technologies Inc. launched a new service called Uber Movement. Designed by a team of 10 engineers, the new service provided a select number of cities access to Uber's vast trove of transportation data. One of the first cities to partner with Uber on this initiative was Washington, DC. Playing directly to the city's longstanding "smart city" aspirations, the initiative was greeted warmly by city officials eager to market the region as a symbol of data-driven urban growth and smart technology. Largely missing from this response, however, was any mention of Uber drivers themselves. Over the course of the paper, and drawing on 40 interviews conducted with Washington, DC-based Uber drivers, we examine the labor conditions that we argue are central to the production of Uber's smart data. Beyond placing labor more centrally in critiques of the smart city, the paper suggests that the experience of Uber drivers offers us a window into the type of smart city on offer. As we argue, the city that emerges from our interviews is less a city defined by data-driven growth, than it is a city defined by alienation and isolation.